Exact solutions on boundary layer flow and heat transfer of carbon nanotubes nanofluids due to non-coaxial rotations - Noranuar, Wan Nura’in Nabilah (2022)
Nanofluid is known as an intelligent engineered fluid which consists of nanometer-sized particles suspended in a conventional base fluid. The development of nanofluid is to enhance the heat transfer capability due to their high thermal conductivity which has attracted numerous researchers’ interest. Moreover, the implementation of nanofluid in rotating systems has been applied in various fields such as engineering field in designing advanced cooling and heating systems and medical field in developing the drug delivery in the human body. This thesis presents four problems of boundary layer flow with heat transfer in a rotating non-coaxial carbon nanofluids. The fluid is considered to be an electrically conducting fluid that flows unsteadily through a porous medium over a moving vertical disk. Hence, the effects of magnetohydrodynamic and porosity are taken into account. The first and second problems are discussed on Newtonian fluid model without and with radiation and mass transfer effects. Meanwhile, the third and fourth problems are discussed on Casson fluid model without and with radiation and mass transfer effects. In this research, water as the Newtonian base fluid and human blood as the Casson base fluid are chosen to suspend nanoparticles of single-wall carbon nanotubes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs). The dimensional governing equations associated with the initial and boundary conditions are converted to the dimensionless form by using appropriate dimensionless variables. By using Laplace transform method, the exact solutions of velocity, temperature, and concentration profiles are obtained. The impact of pertinent parameters such as Casson parameter, Grashof number, modified Grashof number, nanoparticle volume fraction, magnetic field, porosity, radiation, the amplitude of disk, and time on the nanofluid flow, heat and mass transfer are discussed and illustrated graphically. Meanwhile, the skin friction, Nusselt number, and Sherwood number are tabulated in tables. The results show that the fluid with radiation and mass transfer effects has a higher velocity than the fluid without radiation and mass transfer effects. The velocity of Casson nanofluid is higher than Newtonian nanofluid. The flow with a radiation effect has a higher temperature than the flow without radiation. SWCNTs exhibit a lower velocity profile and a higher temperature profile compared to MWCNTs. All the present results are compared to the published results, and the validity of the obtained solutions is confirmed when an excellent agreement is observed. The exactness of the obtained solutions is verified when the comparison of the right-hand side and the left-hand side of the system of equations show an identical value.